A scalp lesion in a newborn baby - Curval, Ana Rita (2021)
A full-term newborn infant born by vaginal delivery presented with an oval skin defect on the parietal scalp measuring 0.5x0.5 cm. The scalp lesion was conservatively managed, with complete epithelization after several weeks. This skin lesion is consistent with the typical appearance of aplasia cutis congenita (ACC) on the scalp. ACC is a rare malformation (present in 1 to 3 in 10,000 live births) characterized by localized absence of certain skin layers, mostly on the scalp, but potentially in any part of the body. ACC etiology remains unclear. Diagnosis is mainly clinical and treatment depends on the presence of complications and the child’s condition. A conservative approach is traditionally used for small defects that heal uneventfully with gradual epithelization, as in the present case.